Methylene Blue versus Coil-Based Computed Tomography-Guided Localization of Lung Nodules - Zhang, Ze-Dong; Wang, Hua-Long; Liu, Xian-Yan; Xia, Feng-Fei; Fu, Yu-Fei (The Thoracic and Cardiovascular Surgeon, 2020)
Background Preoperative computed tomography (CT)-guided localization has been shown to significantly improve lung nodule video-assisted thoracoscopic surgery (VATS)-based wedge resection technical success rates. However, at present, there was insufficient research regarding the optimal approaches to localization of these nodules prior to resection. We aimed to compare the relative clinical efficacy of preoperative CT-guided methylene blue and coil-based lung nodule localization.Methods In total, 91 patients with lung nodules were subjected to either CT-guided methylene blue (n = 34) or coil (n = 57) localization and VATS resection from January 2014 to December 2018. We compared baseline data, localization-associated complication rates, as well as the technical success of localization and resection between these two groups of patients.Results In total, 42 lung nodules in 34 patients underwent methylene blue localization, with associated localization and wedge resection technical success rates of 97.6 and 97.6%, respectively. A total of 71 lung nodules in 57 patients underwent coil localization, with associated localization and wedge resection technical success rates of 94.4 and 97.2%, respectively. There were no significant differences in technical success rates of localization or wedge resection between these groups (p = 0.416 and 1.000, respectively). The coil group sustained a longer duration between localization and VATS relative to the methylene blue group (13.2 vs. 2.5 hours, p = 0.003).Conclusion Both methylene blue and coil localization can be safely and effectively implemented for conducting the diagnostic wedge resection of lung nodules. The coil-based approach is compatible with a longer period of time between localization and VATS procedures.
Keywords: localization; methylene blue; coil; lung nodule